2018
DOI: 10.1111/jvh.12854
|View full text |Cite
|
Sign up to set email alerts
|

Increased recurrence rates of hepatocellular carcinoma after DAA therapy in a hepatitis C‐infected Egyptian cohort: A comparative analysis

Abstract: In Egypt, hepatocellular carcinoma (HCC) is the most common form of cancer and direct-acting antivirals (DAA) are administered on a large scale to patients with chronic HCV infection to reduce the risk. In this unique setting, we aimed to determine the association of DAA exposure with early-phase HCC recurrence in patients with a history of HCV-related liver cancer. This was a prospective cohort study of an HCV-infected population from one Egyptian specialized HCC management centre starting from the time of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 21 publications
4
78
1
Order By: Relevance
“…Moreover, we excluded patients with a history of HCC and those who reported a high rate of HCC recurrence in advance. (7,(40)(41)(42)(43)(44) In the present study, a multivariate analysis showed lower serum zinc levels and higher AFP levels at baseline. As several laboratory parameters changed in patients who achieved SVR following DAA, including reductions in AFP and M2BPGi levels, increases in platelet count, albumin, and serum zinc levels, (28,29,(45)(46)(47) we carried out the multivariate analysis at both baseline and EOT.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, we excluded patients with a history of HCC and those who reported a high rate of HCC recurrence in advance. (7,(40)(41)(42)(43)(44) In the present study, a multivariate analysis showed lower serum zinc levels and higher AFP levels at baseline. As several laboratory parameters changed in patients who achieved SVR following DAA, including reductions in AFP and M2BPGi levels, increases in platelet count, albumin, and serum zinc levels, (28,29,(45)(46)(47) we carried out the multivariate analysis at both baseline and EOT.…”
Section: Discussionsupporting
confidence: 56%
“…The data showed an unexpectedly high rate and pattern of tumor recurrence coinciding with HCV clearance. Other studies (52,53), with similar results, held the shared view that patients receiving DAAs had a greater risk for the recurrence of HCC. Conti et al, also found that after DAA therapy, 17 of 59 (28.8%) patients had HCC recurrence, whereas only nine of 285 (3.16%) patients were diagnosed with HCC for the first time (47).…”
Section: "Hcc Recurrence" In Daa -Treated Patientssupporting
confidence: 59%
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%